2020
DOI: 10.3389/fnagi.2020.00278
|View full text |Cite
|
Sign up to set email alerts
|

Structural Neural Correlates of Double Decision Performance in Older Adults

Abstract: Speed of processing is a cognitive domain that encompasses the speed at which an individual can perceive a given stimulus, interpret the information, and produce a correct response. Speed of processing has been shown to decline more rapidly than other cognitive domains in an aging population, suggesting that this domain is particularly vulnerable to cognitive aging (Chee et al., 2009). However, given the heterogeneity of neuropsychological measures used to assess the domains underpinning speed of processing, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 115 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…This has been explored in young adults, however, showing that more in-scanner motion was related to worse impulse control ( Kong et al, 2014 ). In cognitively healthy aging, older adults experience further declines in cognitive control domains like working memory, inhibition, and flexibility related to changes in brain structure and function ( Evangelista et al, 2021 ; Hausman et al, 2020 ; Kraft et al, 2020 ; Peters, 2006 ; Salthouse, 2010 ). Less cognitive control may influence an individual’s capability to implement a verbal instruction (e.g., “remain still throughout the duration of a scan”), to consistently monitor their head motion, and to suppress distractions from the novel scanning environment (e.g., loud noises).…”
Section: Introductionmentioning
confidence: 99%
“…This has been explored in young adults, however, showing that more in-scanner motion was related to worse impulse control ( Kong et al, 2014 ). In cognitively healthy aging, older adults experience further declines in cognitive control domains like working memory, inhibition, and flexibility related to changes in brain structure and function ( Evangelista et al, 2021 ; Hausman et al, 2020 ; Kraft et al, 2020 ; Peters, 2006 ; Salthouse, 2010 ). Less cognitive control may influence an individual’s capability to implement a verbal instruction (e.g., “remain still throughout the duration of a scan”), to consistently monitor their head motion, and to suppress distractions from the novel scanning environment (e.g., loud noises).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, our exposed subjects also displayed lower processing/psychomotor speed performance. Previous studies also observed significant associations between parahippocampal gyrus thickness and processing speed scores, particularly when working with visuospatial materials (Kraft et al, 2020;Takahashi et al, 2002). Speedy information processing may be crucial for various cognitive functions requiring attention, encoding and retrieval of to-beremembered information, reasoning, decision making, and visuospatial perceptions (Salthouse, 1996).…”
Section: Neuropsychological Features Resembling Alzheimer's Disease A...mentioning
confidence: 86%
“…The underlying mechanism is not clear, but the results are consistent with previous reports of significant associations between parahippocampal gyrus thickness and processing speed scores, particularly when performing visuospatial tasks. 124,125 Speedy information processing may be crucial for various functional abilities including attention, encoding and retrieval of to-be-remembered information, reasoning, decision making, and visuospatial perceptions. 126 Recent structural and functional neuroimaging studies also suggested that the hippocampus may be involved in various neuropsychological tasks such as working memory, executive function, spatial processing, and sensorimotor integration.…”
Section: Neuropsychological Features In Welders May Be Consistent Wit...mentioning
confidence: 99%
“…Glx and GABA concentrations were quantified using a voxel positioned within the prefrontal cortex, which underlies both working memory and speed of processing abilities. Age-related structural declines in the prefrontal cortex have been associated with worse performance on working memory and speed of processing tasks ( Kraft et al, 2020 ; Evangelista et al, 2021 ). Further, 1 H-MRS studies have demonstrated age-related declines in prefrontal GABA and glutamate concentrations, beginning in middle age ( Grachev et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%